Motivation in the workplace and its influence on the effectiveness of work (Journal of Universal Excellence, 2026)
Research Question (RQ): How can we motivate efficiency of the work, which is managed by the individual or the group? Different ways of motivating an individual in an organization?Purpose: The purpose of the research is to determine positive ways of motivation which would allow individuals in different organizations how to improve the efficiency of the work they perform. The aim of the research is the actual use of motivational tools in practice.Method: The article is transparent and theoretical. It is based primarily on an analysis of available domestic and foreign literature and Internet sources on the issues addressed.Results: In this study, it was found that the motivation and efficiency is directly related. Factors are also interdependent, which means that in the case of lack of motivation of employees in an organization there is significant reduced of efficiency. Motivational motives may be monetary (financial rewards) and non-monetary (progression) in nature.Society: The survey can point to the importance of motivation in the workplace.Originality: Originality of research is reflected in the examination of the importance of motivation in the workplace and their influence on these positive results and performance at work.Limitations/Future Research: A further education of managers and leaders in organizations, to realize that with the help of motivated collective we can achieve better excellence and results.
Keywords: motivation; organization; self-efficacy; effectiveness; work